Navigation and localization for a mobile robot in an indoor environment - Zhou, Xiaowei. (2008)
The purpose of the research work presented here was to investigate a mobile robot's navigation and localization problems in an indoor environment. In this research, we adopted the laser scanner as the main sensor for localization and map building.